Narrative branding in support of anthropomorphised personality: A case study of the South African dog influencer industry - Liss, Isabella (Centre for Film and Media Studies, 2025)
The curation of accounts featuring one's dogs form a popular influencer subculture found on Instagram. While dog influencer Instagram accounts avidly portray a branded character, multiple other forms of media have the potential to support anthropomorphised personalities in similar ways. This paper explores links between narrative branding, transmedia storytelling, multimodal media, and framings of agency within the South African dog influencer industry. Through six qualitative interviews with different players in the Cape Town dog influencer industry, the relationship between narrative branding and anthropomorphised personality is examined. These are creators who make use of alternative mediums instead of a traditional influencer Instagram account to promote an anthropomorphised personality for their pets or related business. Most creators incorporate multiple mediums into their work, rather than personifying characters on social media exclusively. These mascots therefore make a case for harnessing the power of multimodal and transmedia narrative structure in advertising, dispersing the canine character across a range of platforms. It must be noted that in this paper, the term “dog influencer” has been extended to anthropomorphised personalities with mediated influence. This is an influence upon the audience which transcends mediums of delivery, so “influencer” is not used solely in reference to social media personalities. Unconventional dog “influencers” include television personalities without adjacent Instagram accounts, and book characters who use social media as a tool to extend their narrative universe.